The Natural History of Anal High-grade Squamous Intraepithelial Lesions in Gay and Bisexual Men. (28th April 2020) - Poynten, I Mary; Jin, Fengyi; Roberts, Jennifer M; Templeton, David J; Law, Carmella; Cornall, Alyssa M; Molano, Monica; Machalek, Dorothy A; Carr, Andrew; Farnsworth, Annabelle; Tabrizi, Sepehr; Phillips, Samuel; et al.
Abstract: Background: Gay and bisexual men (GBM) are disproportionately affected by anal cancer. Prevention is hindered by incomplete understanding of the natural history of its precursor, anal high-grade squamous intraepithelial lesions (HSIL). Methods: The Study of the Prevention of Anal Cancer, conducted between 2010 and 2018, enrolled human immunodeficiency virus (HIV)-positive and HIV-negative GBM aged ≥35 years. Anal cytology and high-resolution anoscopy (HRA) were performed at baseline and 3 annual visits. A composite HSIL diagnosis (cytology ± histology cHSIL) was used. Cytological high-grade squamous intraepithelial lesions (cHSIL) incidence and clearance rates were calculated with 95% confidence intervals (CIs). Predictors were calculated using Cox regression with hazard ratios (HRs) and 95% CIs. Results: Among 617 men, 220 (35.7%) were HIV-positive, median age 49 years. And 124 incident cHSIL cases occurred over 1097.3 person-years (PY) follow-up (11.3, 95% CI 9.5–13.5 per 100 PY). Significant bivariate predictors of higher incidence included age <45 years (HR 1.64, 95% CI 1.11–2.41), HIV positivity (HR 1.43, 95% CI .99–2.06), prior SIL diagnosis ( P -trend < .001) and human papillomavirus (HPV)16 (HR 3.39, 2.38–4.84). Over 695.3 PY follow-up, 153 cHSIL cleared (clearance 22.0, 95% CI 18.8–25.8 per 100 PY). Predictors were age < 45 years (HR 1.52, 1.08–2.16), anal intraepithelial neoplasia (AIN)2 rather than AIN3 (HR 1.79, 1.29–2.49), smaller lesions (HR 1.62, 1.11–2.36) and no persistent HPV16 (HR 1.72, 1.23–2.41). There was 1 progression to cancer (incidence 0.224, 95% CI .006–1.25 per 100 PY). Conclusion: These data strongly suggest that not all anal HSIL detected in screening requires treatment. Men with persistent HPV16 were less likely to clear HSIL and are more likely to benefit from effective HSIL treatments. Clinical Trials Registration: Australia New Zealand Clinical Trials Registry (ANZCTR365383). Abstract : Anal high-grade squamous intraepithelial lesions (HSIL) is a dynamic condition in gay and bisexual men. One in ten men developed incident HSIL and one in five men spontaneously cleared HSIL, per year. There was one case of progression to cancer, a rate of one in 446 person-years.